Managing and Negotiating Cultural Identity: The Adaptive Dynamics of Jaranan Thik in Ponoragan Society - Oki Cahyo Nugroho; Widodo Muktiyo; Sri Hastjarjo; Drajat Tri Kartono (Jogjakarta Communication Conference (JCC), 2026)
This study investigates how Jaranan Thik negotiates cultural identity and adapts communicatively within the Reyog-centered cultural hierarchy of Ponorogo, East Java, Indonesia. Grounded in Cultural Identity Theory and Co-Cultural Communication Theory, it analyzes how a marginalized traditional art community strategically navigates identity through symbolic alignment, structural adjustment, and engagement with institutional actors. Employing a qualitative case study design, the research draws on in-depth interviews with performers, cultural leaders, and community representatives, complemented by documentation and direct observation of performances. The findings identify four key patterns: symbolic assimilation via shared mythological references and terminology; the regulated reframing of trance practices to reshape public perception; religious and institutional affiliations to strengthen moral and structural legitimacy; and aesthetic innovation to attract younger audiences. These adaptive strategies indicate that Jaranan Thik does not merge into the dominant Reyog tradition but instead negotiates recognition through selective alignment while maintaining its essential ritual foundations. By situating the analysis within localized cultural hierarchies, the study broadens the scope of Cultural Identity Theory and Co-Cultural Communication Theory and underscores communicative agency as vital to cultural sustainability.